Estimation of P (X È Y) for discrete distributions with non-identical support - Mriganka Mouli Choudhury; Rahul Bhattacharya; Sudhansu S. Maiti (Statistics in Transition new series (SiTns), 2022)
The Uniformly Minimum Variance Unbiased (UMVU) and the Maximum Likelihood (ML) estimations of R = P(X È Y) and the associated variance are considered for independent discrete random variables X and Y. Assuming a discrete uniform distribution for X and the distribution of Y as a member of the discrete one parameter exponential family of distributions, theoretical expressions of such quantities are derived. Similar expressions are obtained when X and Y interchange their roles and both variables are from the discrete uniform distribution. A simulation study is carried out to compare the estimators numerically. A real application based on demand-supply system data is provided.
Keywords: 519; stress-strength model; uniformly minimum variance unbiased; maximum likelihood